Resistance and Revolution in the Age of Authoritarian Revanchism: The Power of Revolutionary Imaginaries in the Austerity-Security State Era. (June 2019) - Selbin, Eric
We live in an age of authoritarian revanchism, an era of Austerity-Security States often voted in by a set of fears stoked by elites that economies require patriarchal, conserving policies. Hence the end of state welfare functions, destruction of stable employment and unclear job futures create profound economic fear even as the destruction of communal bonds such as identities, social protections and sense of place have produced deep social dread. Resistance, rebellion and revolution remain ready and apt responses for people all around the world. Recent academic interest in 'imaginaries' – social, cultural, technological, psychological and more – reflect a renewed appreciation for human agency, collective action, ideology, cultural matters and the 'narrative turn'. Rich revolutionary imaginaries, often daring acts of bricolage, provide people with the means and methods to struggle for control of the material and ideological conditions of their everyday lives even in the face of forces inimical to their interests. What could be more meaningful than changing the small worlds that are our everyday worlds and hence matter most for most of us most of the time? Where, when, and who will bring revolution into the 21st Century? A broader, deeper definition will help to ascertain, explore and explicate. Resistencia y revolución en la época del revanchismo autoritario: el poder de los imaginarios revolucionarios en la era de la austeridad-seguridad